Protective effect of esketamine on hepatic ischemia-reperfusion injury - DU Shuyao, LYU Jing, ZHOU Ziyu, FENG Guangwu, LUO Xianghong (Zhongguo linchuang yanjiu)
Esketamine, as a perioperative sedative and analgesic drug, has been widely used in Europe and America. However, the protective effect of esketamine on the liver during the perioperative period is still in the applicated research stage. This article briefly introduces the efficacy, mechanism of action, and research progress of esketamine in hepatic ischemia-reperfusion, in order to provide a medication reference for clinical staff in this field.